2009
DOI: 10.1097/mrr.0b013e32831e4546
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in limb kinetic apraxia by repetition of a newly designed facilitation exercise in a patient with corticobasal degeneration

Abstract: Corticobasal degeneration is a progressive neurological disorder characterized by a combination of parkinsonism and cortical dysfunction such as limb kinetic apraxia, alien limb phenomenon, and dementia. To study the effect of repetitive facilitation exercise (RFE) in a patient with corticobasal degeneration, we used a newly designed facilitation exercise designed to elicit movements isolated from the synergy in hemiplegia. This exercise included movements of each isolated finger using stretch reflex and skin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 6 publications
0
31
0
Order By: Relevance
“…The authors suggested that RFE may have prevented a decrease of neuronal or neural circuit loss. 15 No other evidence describing the effects of exercise in clients with CBD was found in the literature.…”
Section: Long-term Exercise Training For An Individual With Mixed Cormentioning
confidence: 97%
See 1 more Smart Citation
“…The authors suggested that RFE may have prevented a decrease of neuronal or neural circuit loss. 15 No other evidence describing the effects of exercise in clients with CBD was found in the literature.…”
Section: Long-term Exercise Training For An Individual With Mixed Cormentioning
confidence: 97%
“…A case report described the effects of repetitive facilitation exercise (RFE) combined with occupational therapy in a single client with CBD. 15 Following 4 weeks of these exercises, both activities of daily living and finger motor function improved. The authors suggested that RFE may have prevented a decrease of neuronal or neural circuit loss.…”
Section: Long-term Exercise Training For An Individual With Mixed Cormentioning
confidence: 98%
“…Furthermore, previous studies have focused on acquisition of a new task, but not improving performance in the same task, which is usually achieved in motor rehabilitation. The simple test for evaluating hand function (STEF) is a standardized test for upper-extremity functions, in which the time required for completing repetitive manual tasks is measured (Yamanaka et al, 2005; Kawahira et al, 2009). In the present study, we investigated a role of the aDMPFC in performance improvement during repetitive STEF in healthy subjects using functional near infrared spectroscopy (fNIRS).…”
Section: Introductionmentioning
confidence: 99%
“…The repetitive facilitation exercises (RFEs) using these novel facilitation methods for the upper limb and fingers, as shown in Figure 1, give sufficient physical stimulation, such as by the stretch reflex or skin-muscle reflex that is elicited immediately before or at the same time as when the patient makes an effort to move his hemiplegic hand or finger, in order to elevate the level of excitation of the corresponding injured descending motor tracts and it allows the patient to initiate movements of the hemiplegic hand or finger in response to his intention. The functional improvements seen with repetitive training of finger flexion and extension for the hemiparetic hand [17] and with RFEs for the hemiplegic lower limb [18] and for limb kinetic apraxia of the upper limb and fingers [19] have suggested that functional recovery of the hemiplegic upper limb and hand might depend on repetition of voluntary movements elicited by the RFEs, especially when they are influenced by a synergic pattern.…”
Section: Introductionmentioning
confidence: 99%